PENGARUH WORK LIFE BALANCE DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PADA SUKU DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA ADMINISTRASI JAKARTA PUSAT: Studi Kasus Pada SUKU DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA ADMINISTRASI JAKARTA PUSAT - Zhulia Choirun Nisa (Jurnal Manajemen, 2025)
Human resources are a crucial component influencing the success of an institution, particularly government institutions. This study aims to analyse the impact of work-life balance and work load on employee performance at the Population and Civil Registration Office of the Jakarta Central Administrative City. Employees face dynamic workloads, making work-life balance a significant challenge. The method used is quantitative with a descriptive approach. Data collection techniques included observation, interviews, and the distribution of questionnaires to 43 respondents using a saturated sampling method. Data processing was conducted using SPSS version 26, with a series of statistical tests including: validity tests, reliability tests, classical assumption tests, multicollinearity tests, heteroskedasticity tests, hypothesis tests (t-test and F-test), multiple linear regression tests, and determination coefficient tests (partial and simultaneous). The test results showed that all instruments were valid and reliable. The variables Work-Life Balance and Workload each had a significant partial effect on Employee Performance with a t-value of 3.842 > t-table 1.684 and a Sig. value < 0.05. Meanwhile, the simultaneous test yielded an F-calculated value of 12.382 > F-table 3.23 with Sig. 0.000, meaning that both variables together have a significant effect on Employee Performance. The simultaneous coefficient of determination (R²) of 0.382 indicates that 38.2% of the variation in performance is explained by the two independent variables. Keywords: Human Resources, Work-Life Balance, Workload, Employee Performance